Industry Modern: A Solution for Sustainable Business Performance's Technology Challenges - Alyusha Asmolov; Avraam Ledentsov (Aptisi Transactions On Technopreneurship (ATT), 2022)
Due to a lack of resources and other market issues, technology adoption is always a difficult task for Small and Medium-Sized Enterprises (SMEs).The sustainable business performance of SMEs is adversely affected by numerous technological obstacles.Industry 4.0, on the other hand, has the potential to resolve a number of technology issues.Industry 4.0 seeks to achieve a higher level of automation in addition to a higher level of operational effectiveness and productivity.Therefore, the goal of this study is to determine how Industry 4.0 can help SMEs in Thailand achieve sustainable business performance.Using Partial Least Square, data from managers of SMEs have been gathered through the preparation of a survey.The questionnaire was used to collect the data, and simple random sampling was used to distribute the questionnaires.A total of 500 questionnaires were distributed to Thai small and medium-sized enterprises' managerial staff.280 of the questionnaires were returned, and 270 of the responses were found to be legitimate.Partial Least Square (PLS)-Structural Equation Modeling (SEM) was used to analyze the data.According to the findings, one of the keys to the development of sustainable business performance among SMEs is Industry 4.0.Big data, the Internet of Things, and the smart factory are examples of Industry 4.0 elements that help to encourage the use of information technology (IT), which improves long-term business performance. Additionally, the positive connection between IT implementation and Industry 4.0 is bolstered by organizational structure and procedure.